Semiotika Komersialisasi Islam: Analisis Produk Iklan “Resik V Keluarga Sakinah” di Televisi - Koirudin, Kolik; Habsari, SettingsSri Kusuma; Ardianto, Deny Tri (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This article aims to analyse the meaning of the construction of Islam in the